MRI diffusion phantoms: ADC and relaxometric measurement comparisons between polyacrylamide and agarose gels. Issue 139 (June 2021) - Boursianis, T.; Kalaitzakis, G.; Pappas, E.; Karantanas, A.H.; Maris, T.G.
Abstract: Purpose: The aim of this study is to compare polyacrylamide and agarose gels, as components of a simple MRI phantom, for the measurements of Apparent Diffusion Coefficient (ADC), T1 and T2 relaxation times. Materials and methods: Five (5) test tubes with polyacrylamide gels of different monomer concentrations and six (6) test tubes of different agarose gel concentrations were used as a phantom for ADC, T1 and T2 measurements, which were expressed as 2D color parametric maps, on a 1.5 T clinical MRI system. ADC and T2 maps were calculated utilizing a Weighted Linear (WL) regression fitting algorithm. T1 maps were calculated utilizing a standard non-linear fitting algorithm. Results: In agarose gels, ADC measurements are independent of the agarose concentration, whereas the T1 and T2 relaxation times decrease with increasing agarose concentration. On the contrary, in polyacrylamide gels, ADC measurements decrease quadratically while increasing the monomer concentration, whereas the T1 and T2 relaxation times reveal a linear decrease with increasing monomer concentration. Conclusion: Polyacrylamide gels can serve as a better means for simulating ADC values, as compared with the agarose gels used in this study.